THE INFLUENCE OF EMPLOYEE COMPETENCE AND TRANSFORMATIONAL LEADERSHIP ON THE EFFECTIVENESS OF DISPUTE RESOLUTION BASED ON BAPPEBTI REGULATIONS IN THE FIELD OF COMMODITY FUTURES TRADING - Hary Lesmana; Zulkifli Rangkuti; Hadi Purnomo (Yayasan Pendidikan Cahaya Budaya Indonesia, 2026)
This study aims to analyze the influence of employee competence and transformational leadership on the effectiveness of dispute resolution based on the Commodity Futures Trading Regulatory Agency (BAPPEBTI) regulations in the field of commodity futures trading. The problem in this study stems from the obstacles still found in the dispute resolution process, such as slow case handling, less than optimal employee understanding of regulations, and the less than optimal implementation of leadership that can drive improved organizational performance. This study uses quantitative methods with a descriptive and associative approach. Data collection techniques were carried out by distributing questionnaires to respondents involved in the dispute resolution process in the commodity futures trading environment. Data analysis used validity and reliability tests, multiple linear regression, t-tests, F-tests, and coefficients of determination. The results of the study indicate that employee competence and transformational leadership have a positive and significant effect on the effectiveness of dispute resolution, both partially and simultaneously. These findings indicate that improving employee capabilities, regulatory understanding, communication, motivation, and visionary and inspirational leadership can support the creation of a more effective, efficient dispute resolution process that is in accordance with BAPPEBTI regulations in the field of commodity futures trading.